2018
DOI: 10.1002/aur.1971
|View full text |Cite
|
Sign up to set email alerts
|

Atypical longitudinal development of functional connectivity in adolescents with autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is consistently associated with alterations in brain connectivity, but there are conflicting results as to where and when individuals with ASD display increased or reduced functional connectivity. Such inconsistent findings may be driven by atypical neurodevelopmental trajectories in ASD during adolescence, but no longitudinal studies to date have investigated this hypothesis. We thus examined the functional connectivity of three neurocognitive resting-state networks – the defaul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 91 publications
(141 reference statements)
4
27
0
Order By: Relevance
“…In contrast, they found that disrupted connectivity between DMN and salience network was more characteristic of EOP, whereas in ASD the atypical connections were primarily found within the salience network. Studies examining the maturational trajectory of resting state networks in ASD suggest that DMN connectivity appears to decrease from childhood to adolescence (73,84,100), similar to the DMN "network pruning" found in studies of typically developing adolescents (36,37,41,45). However, unlike typically developing adolescents, there is a lack of both strengthening between anterior and posterior hubs of the DMN and segregation from other brain regions reported during this developmental period in the reviewed ASD studies.…”
Section: Shared and Distinct Dmn Connectivity Patterns In Adolescentsmentioning
confidence: 55%
“…In contrast, they found that disrupted connectivity between DMN and salience network was more characteristic of EOP, whereas in ASD the atypical connections were primarily found within the salience network. Studies examining the maturational trajectory of resting state networks in ASD suggest that DMN connectivity appears to decrease from childhood to adolescence (73,84,100), similar to the DMN "network pruning" found in studies of typically developing adolescents (36,37,41,45). However, unlike typically developing adolescents, there is a lack of both strengthening between anterior and posterior hubs of the DMN and segregation from other brain regions reported during this developmental period in the reviewed ASD studies.…”
Section: Shared and Distinct Dmn Connectivity Patterns In Adolescentsmentioning
confidence: 55%
“…In addition, the work has been limited by small sample sizes and problems with replication that is likely caused by the many challenges with MRI data collection in people with autism, such as differences in data processing, intersubject variability and data quality 80 . Longitudinal imaging 81 as well as associating neuroimaging data with longitudinal behavioural outcomes 82 can address some of these limitations characterizing differences within participants.…”
Section: [H2] Geneticsmentioning
confidence: 99%
“…Approximately 52% of the studies in adolescents with ASD presented in our review (Table 1 and 2) have utilized the ABIDE dataset to investigate DMN connectivity (Nielsen et al, 2014;Nomi and Uddin, 2015;Elton et al, 2016;Falahpour et al, 2016;Ypma et al, 2016;Chen et al, 2017;Guo et al, 2017;Bi et al, 2018;Kernbach et al, 2018;Borras-Ferris et al, 2019;Guo et al, 2019;Lawrence et al, 2019;Reiter et al, 2019;Wang et al, 2019a). About half of the studies (15 out of 29) in adolescents with ASD have found a global pattern of underconnectivity both within the DMN hubs (Assaf et al, 2010;Weng et al, 2010;Starck et al, 2013;Falahpour et al, 2016;Ypma et al, 2016;Neufeld et al, 2018;Borras-Ferris et al, 2019;Reiter et al, 2019), as well as between the DMN and other brain regions such as insula, subcortical regions, fronto-parietal regions, and visual cortex (Wiggins et al, 2011;Nielsen et al, 2014;Nomi and Uddin, 2015;Kernbach et al, 2018;Guo et al, 2019), regardless of analytic methods used.…”
Section: Dmn Connectivity In Adolescents With Asdmentioning
confidence: 99%
“…Relatively fewer studies (five out of 29) have observed over-connectivity between the DMN and task-positive regions within the frontoparietal, visual, and sensorimotor regions, as well as the salience network (Redcay et al, 2013;Elton et al, 2016;Hogeveen et al, 2018;Gao et al, 2019;Mash et al, 2019). Some studies (nine out of 29) have additionally found mixed patterns involving under-and over-connectivity of ASD youth relative to typically developing (TD) controls, largely highlighting a pattern of within-DMN underconnectivity, with overconnectivity between DMN and other networks such as task-positive or sensorimotor networks (Doyle-Thomas et al, 2015;Jann et al, 2015;Abbott et al, 2016;Chen et al, 2017;Guo et al, 2017;Joshi et al, 2017;Bi et al, 2018;Pereira et al, 2018;Lawrence et al, 2019;Wang et al, 2019a). This mixed pattern of connectivity may suggest poor integration within the DMN, along with atypical segregation between the DMN and other related cognitive networks in adolescents with ASD (see Table 2 for main results from each study).…”
Section: Dmn Connectivity In Adolescents With Asdmentioning
confidence: 99%
See 1 more Smart Citation